EFFECTS OF MILDRONATE, AS A PART OF COMBINED HEART FAILURE THERAPY, ON CARBOHYDRATE AND LIPID METABOLISM AND OXIDATIVE STRESS PARAMETERS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - M. E. Statsenko; S. V. Turkina; S. V. Belenkova; L. V. Poletaeva; G. P. Dudchenko (Российский кардиологический журнал, 2010)
In total, 100 patients aged 45-70 years, with Functional Class (FC) II-III chronic heart failure (CHF) and compensated or sub-compensated Type 2 diabetes mellitus (DM-2) were examined. All participants were randomised into two groups, including 50 individuals each. In the main group, the standard CHF therapy was combined with mildronate treatment (1,0 g/d). The study lasted for 12 weeks. In DM-2 patients, adding a cardioprotective agent mildronate to complex CHF therapy was associated with improved carbohydrate and lipid metabolism, significantly reduced oxidative stress, reduced CHF FC, increased physical stress tolerability, anti-anginal effect, and improved quality of life.